Immigrants italiens et frontière américaine : Pioneers ! Ο pioneers ! - Marie-Christine Michaud (Anglophonia)
Between the Civil War and the First World War most of the Italian immigrants settled in Eastern cities. Nonetheless some of them chose to go West. They were pulled there by the myth of liberty, and also by job opportunities in mines, on the construction of the railroad and on farms. Ironically, these Italians acquired a new identity based on their adaptation to the environment. As a matter of fact, they were building American society and felt they were part and parcel of the pioneers who spread American civilization in the new territories. Hence they lived in a new "western identity space," and became pioneers—Italian-American pioneers.